Raw Material Scarcity and Overproduction in the Food Industry - Sharma, Suresh D.; Bhagat, Arpan R.; Parisi, Salvatore (Chemistry of Foods, 2019)
This book describes the consequences of an increased demand for food for human consumption for the global food industry. In four concise chapters, the authors explore the trend for the overproduction of food, the concomitant diminution of raw materials and the increase in environmental concerns. Chapter one describes the variations in biochemical properties of fishmeal depending on the season and geographical location. Chapter two discusses how the expansion of cropland and pastures to meet the rising demand for food is damaging the environment, while chapter three examines the impact of bee viruses on food crops and production. Lastly, the fourth chapter addresses the issue of food adulteration and provides specific examples of fraud in the American dairy industry. This book is of interest to researchers working in the area of food production in academia and industry, as well as certification and scientific bodies involved in food inspection.